2020
DOI: 10.1177/0300060520936082
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functions of policosanol in elderly patients with dyslipidemia

Abstract: Objective To determine the multiple functions of policosanol in elderly dyslipidemia patients. Methodology: There were 294 elderly dyslipidemia patients enrolled into this clinical study. They were randomly divided into four groups, as follows: 20 mg policosanol (group A, n = 64); 10 mg policosanol (group B, n = 72); 20 mg atorvastatin (group C, n = 91); and 10 mg policosanol + 20 mg atorvastatin (group D, n = 62). Plasma platelet count, platelet aggregation rate, circulating endothelial cell (CEC) count, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Policosanol is a mixture of aliphatic alcohols ranging from 24–34 carbon atoms [ 1 , 2 ], such as octacosanol, triacontanol, dotriacontanol, hexacosanol, and tetratriacontanol, which are purified from sugar cane ( Saccharum officinarum L.) wax [ 1 , 2 , 3 ] or various plants, such as oats [ 4 ], barley [ 5 ], insects [ 6 , 7 ], and bees wax [ 8 ]. Many policosanols from different sources have been claimed to treat blood dyslipidemia [ 9 , 10 ], diabetes [ 11 ], hypertension [ 12 , 13 ], and dementia [ 14 , 15 ] by raising the HDL-C level and lowering the LDL-C level. However, with the exception of Cuban policosanol [ 12 , 16 , 17 ], there is insufficient information on policosanol regarding its compositions and physiological effects on the lipoprotein metabolism, particularly in HDL functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Policosanol is a mixture of aliphatic alcohols ranging from 24–34 carbon atoms [ 1 , 2 ], such as octacosanol, triacontanol, dotriacontanol, hexacosanol, and tetratriacontanol, which are purified from sugar cane ( Saccharum officinarum L.) wax [ 1 , 2 , 3 ] or various plants, such as oats [ 4 ], barley [ 5 ], insects [ 6 , 7 ], and bees wax [ 8 ]. Many policosanols from different sources have been claimed to treat blood dyslipidemia [ 9 , 10 ], diabetes [ 11 ], hypertension [ 12 , 13 ], and dementia [ 14 , 15 ] by raising the HDL-C level and lowering the LDL-C level. However, with the exception of Cuban policosanol [ 12 , 16 , 17 ], there is insufficient information on policosanol regarding its compositions and physiological effects on the lipoprotein metabolism, particularly in HDL functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the intake of policosanol can be regulated by whole grains, nonpeeled fruits, or policosanol supplements. Aral administration of policosanol can significantly improve obesity and reduce triglyceride and cholesterol levels, whereas no significant toxicological effect has been reported in human and mouse models (Li et al., 2020; Tian & Acevedo, 2020). As indicated from the metabolic flow analysis, after the absorption into the body, policosanol is mainly distributed in the liver tissue, followed by adipose tissue and muscle, which demonstrates that its main target tissue is liver (Kabir & Kimura, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that Policosanol, in addition to preventing endothelial damage, significantly reduces the thickness of the intima in rabbit arteries previously damaged by forceps [47]. The experimental results were confirmed in a double-blind, controlled clinical trial in hypercholesterolemic elderly patients, treated with policosanol, in whom a reduction in circulating endothelial cells was observed [48].…”
Section: Antiapoptotic Effectsmentioning
confidence: 76%